2022
DOI: 10.3390/drones6050109
|View full text |Cite
|
Sign up to set email alerts
|

Drone Usage for Medicine and Vaccine Delivery during the COVID-19 Pandemic: Attitude of Health Care Workers in Rural Medical Centres

Abstract: Rural areas are often difficult to access reliably with medicine and vaccines. This study aimed to examine rural health care workers’ attitude towards drone delivery for medicine and vaccines and the factors that influenced it. Health care workers from four rural health care facilities were sampled. Participants self-reported their demographic information, attitude towards medicine and vaccine delivery using drones, perception of benefits and risks of using drones, and perceived leadership innovativeness throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Drones make it possible to transport goods from point A to point B in a delivery service [ 165 , 166 , 167 , 168 ]. It is also possible to transport medical goods or blood, in compliance with existing regulations [ 152 , 153 , 160 , 169 , 170 , 171 , 172 ]. There are many opportunities for commercial use of drones; an overview using Australia as an example can be found in [ 173 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drones make it possible to transport goods from point A to point B in a delivery service [ 165 , 166 , 167 , 168 ]. It is also possible to transport medical goods or blood, in compliance with existing regulations [ 152 , 153 , 160 , 169 , 170 , 171 , 172 ]. There are many opportunities for commercial use of drones; an overview using Australia as an example can be found in [ 173 ].…”
Section: Resultsmentioning
confidence: 99%
“…Drone users are not only people who choose this parcel delivery method, but also health care workers, and their doubts and opinions must be considered when designing a UAV system for medical use [ 160 , 170 ].…”
Section: Resultsmentioning
confidence: 99%
“…Drones will guarantee faster, eco-friendlier, and cost effective COVID-19 vaccine delivery compared to traditional delivery methods such as vans and trucks. Access to the predominantly difficult-to-access rural areas in LMICs will also be easier with drones [25] . Drones have been used in different settings to supply medicines, medical supplies and other vaccines.…”
Section: The Role Of Research and Academia In Post Covid-19 Recoverymentioning
confidence: 99%
“…Therefore, it is particularly important that all user groups are involved at an early stage. Furthermore, after a recent scoping review showed that there were no empirical studies on user acceptance of drone-based medication delivery [ 7 ], we could only find 1 study in Asia that investigated user acceptance among health care professionals in the delivery of drone-based medication [ 8 ]. The successful application of technology is predominantly determined by the type and extent of acceptance [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%